The Difference Incidence of Maternal Uterine Inertia Between Labor With and Without Anemia in Hospital of dr. Soebandi Jember - Dina Ayu Savitri; Yonas Hadisybroto; Pipiet Wulandari (Faculty of Medicine, University of Jember, 2019)
One of the indirect causes of maternal death is anemia. Anemia in pregnancy is a woman with a hemoglobin level below 11 g / dl caused by iron deficiency in pregnant women so that the hemoglobin level becomes low and cannot meet the need for oxygen to perfusion to the tissues. This consumes energy in the affected muscles and buildup of lactic acid which causes fatigue and reduced muscle contraction during labor. Inadequate uterine contractions are called uterine inertia and are characterized by a prolonged phase of labor, which is weak, rarely and short duration. The purpose of this study was to determine the differences in the incidence of uterine inertia between labor and anemia released in RSD dr. Soebandi Jember. This study was analytic observational with a cross sectional research design. The study population was all pregnant women who had improved labor and were included in the medical record at RSD Dr. Soebandi Jember period January 1, 2017 - December 31, 2017. Samples from this study were mothers who had approved the delivery and fulfilled the inclusion and exclusion criteria that had been determined until the number of samples could be fulfilled. The number of samples in this study were 76 samples. The type of data used in this study is secondary data obtained by researchers from the medical records of pregnant women who have received labor. The data included in this study contain demographic data consisting of the age of pregnant women and parity, clinical data in the form of uterine inertia and laboratory data consisting of anemia status. In analyzing the data with Chi Square test (X²), a significance value of 0.011 was obtained so that it can be concluded that Ho is rejected and Ha is accepted which means that the incidence of uterine inertia between free labor and anemia is not important in RSD Dr. Soebandi Jember. Keywords: anemia, uterine inertia, pregnancy, age, parity.